Role of capsaicin sensitive nerves in epidermal growth factor effects on gastric mucosal injury and blood flow. Issue 3 (1st March 1998) - Kang, J Y; Teng, C H; Chen, F C; Wee, A
Abstract : Background —Epidermal growth factor (EGF) and capsaicin protect against experimental gastric mucosal injury. Capsaicin exerts its gastroprotective effect by stimulating afferent neurones leading to release of calcitonin gene related peptide (CGRP) which causes gastric hyperaemia. EGF also causes gastric hyperaemia but whether it acts via capsaicin sensitive neurones is unknown. Aims —To assess the influence of: (1) capsaicin desensitisation on EGF effects on gastric mucosal injury and gastric mucosal blood flow; and (2) close arterial infusion of hCGRP8–37, a CGRP antagonist, on EGF effects on gastric mucosal blood flow. Methods —The absolute ethanol induced gastric mucosal injury model in the rat was used. Gastric mucosal damage was assessed by planimetry and light microscopy. Gastric mucosal blood flow was measured by laser Doppler flowmetry in a gastric chamber preparation. Results —Capsaicin desensitisation abolished the gastroprotective and gastric hyperaemic effects of EGF. Close arterial infusion of hCGRP8–37 antagonised the hyperaemic effect of both capsaicin and EGF. Conclusion —Results show that EGF may exert its gastroprotective and gastric hyperaemic effects via capsaicin sensitive afferent neurones.